30-day readmission rate in pediatric otorhinolaryngology inpatients: a retrospective population-based cohort study - Katharina Geißler; Wido Rippe; Daniel Boeger; Jens Buentzel; Kerstin Hoffmann; Holger Kaftan; Andreas Mueller; Gerald Radtke; Orlando Guntinas-Lichius (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objectives Analysis of frequency and reasons for planned and unplanned 30-day readmission in hospitalized pediatric otorhinolaryngology patients using German Diagnosis Related Group (G-DRG) system data. Methods A retrospective population-based cohort study in Thuringia, Germany, was performed for the year 2015 with 2440 cases under 18 years (55.6% male) out of a total number of 15.271 inpatient cases. The majority of pediatric patients were from 2 to 5 years old (54.5%). The most frequent diagnoses were hyperplasia of adenoids or/and tonsils (26.6%). 36 cases (1.5%) experienced readmission within 30-days. Results 30-day readmission was planned in 9 cases (25% of all readmission) and was unplanned in 27 cases (75%). The median interval between index and readmission treatment was 8 days. Postoperative bleeding after adenoidectomy, tonsillotomy/tonsillectomy or tracheostomy (33.4%) and infectious complications after surgery like acute otitis media, abscess formation or fever (36.2%) were the most frequent reasons for 30-day readmission. Compared to adults treated in 2015 in Thuringia, the readmission rate was higher in adult patients (8.9%) than in this pediatric cohort. In contrast to children, readmissions in adults were mainly planned (65.1%) with a different spectrum of underlying diseases and reasons for readmission. Conclusion The 30-day readmission rate seemed to be lower for pediatric otolaryngology patients compared to adult patients. Unplanned readmissions dominated in pediatric patients, whereas planned readmissions dominated in adults.